Sharecropping system and labor market in the Dona Francisca colony: new evidences on european colonization in southern Brazil in the transition from slavery, 1851-1876 - pt, pt (Estudos Econômicos (São Paulo), 2024)
This article examines the labor market in the Dona Francisca colony, one of the most important centers of European colonization from Brazil in the nineteenth century. The analyse has shown new evidences about the use of immigrant labor force during the transition of slavery in Brazil. Specially, the article has revealed the use of sharecropping system like a way of free work in the settlement of small owners Dona Francisca, in South of Brazil. Besides this one, this study shows that, this study shows that despite the high land-labor ratio and the fact that the Dona Francisca settlers were small landowners, the majority of stablished immigrants worked on paid activities which were parallel to the agriculture, dedicating themselves only and partially to it in their properties. Thus, the evidence presented in this article suggests that the labor market in the Dona Francisca colony had been one exception in relation to formulated Evsey Domar`s hypothesis, in known published article from 1970.